Valor nutritivo do milho opaco-2 para suínos - Melgaço A. Costa, Paulo; Vaz de Mello, Hélcio; B Mayrose, Vernon; Magno Pato, José (Revista Ceres, 2025)
Three experiments, involving 63 weaning pigs and 32 pigs from 4 to 5 months of age (average live weight of 55 kg), were conducted to evaluate the nutritive value of opaque-2 corn in growing and finishing rations for swine.